GOOD CORPORATE GOVERNANCE (GCG) AND TALENT ANALYSIS MANAGEMENT FROM EMPLOYEE PERSPECTIVE - Gunawan Sukianto; Lusy Lusy (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Human resources play an important role for driving the company. Companies that can mobilize their employees in maximizing their duties can reduce the negative impact of environmental factors, and will improve the company's financial performance. The purpose of this study is to analyze the role of applied GCG and Talent Management from an employee perspective, a case study of BPR Bakti in Sidoarjo. This study uses a qualitative descriptive approach, because it wants to solve problems related to employee performance at BPR Bakti, seen from the implementation of Good Corporate Governance and Talent Management. The stages of this research: (1) identify the role of GCG; (2) identify the role of Talent Management; (3) Identification of employee performance; and (4) analysis of the role of GCG and Talent Management in the context of developing effective employee performance. Based on the results of the study, it shows that the company has not implemented GCG related to employee performance, openly, and has not implemented Talent Management. The company also has not compiled employee personal development in the form of training and has not mapped the competencies of each employee, and there is no guidance, education and empowerment for employees as future leaders. The measurement of employee performance indicators is also not owned by the BPR, so there is no evaluation or assessment of employee performance. The factor that supports the performance of this BPR is the loyalty of the employees who work there. Keywords: Good Corporate Governance, Talent Management, Performance